A simpler prescription to calculate MHV amplitudes for gravitons at tree level in superstring theory - Ursulino, Tiago Pinheiro [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In this work we review the simple formulas found for MHV amplitudes of gluons and gravitons inside the contexts of super-Yang-Mills with supersymmetry N = 4 and supergravity with supersymmetry N = 8. We then review the prescription proposed by Berkovits and Maldacena [5] which simpli?es the calculation of those amplitudes for gluons inside the context of open superstrings, and which reproduces the correct results for 4 and 5 gluons, besides reducing to the sYM results in the 'alfa linha' = 0 limit, as veri?ed in [5] and [22]. Next, we extend the Berkovits-Maldacena prescription to the closed superstring, using it ?rst to calculate the MHV amplitude for 4 gravitons and verifying the result with the ones found in the literature by usual methods (result already obtained in [8]). As an original contribution to the subject, we will prove that, in the 'alfa linha' = 0 limit, the prescription gives the result of supergravity found by Hodges [17]

Neste trabalho relembramos as fórmulas simples encontradas para as amplitudes MHV de gluons e gravitons nos contextos de super-Yang-Mills com supersimetria N = 4 e de supergravidade com supersimetria N = 8. A seguir, relembramos a prescrição proposta por Berkovits e Maldacena [5] que facilita o cálculo dessas amplitudes para gluons no contexto de supercordas abertas, e que reproduz os resultados corretos para 4 e 5 gluons além de se reduzir aos resultados de sYM no limite 'alfa linha' = 0, conforme veri?cado em [5] e [22]. Em seguida, estenderemos a prescrição de Berkovits-Maldacena para a supercorda fechada, usando-a primeiramente para calcular a amplitude MHV de 4 gravitons e conferindo o resultado com os encontrados na literatura por métodos usuais (resultado já obtido em [8]). Como contribuição original ao tema, demonstraremos que, no limite 'alfa linha' = 0, a prescrição reproduz o resultado de supergravidade encontrado por Hodges [17]
Keywords: Teoria de Yang-Mills; Supergravidade; Teoria das supercordas